CONTINUITY OF MIDWIFERY CARE FOR MRS. P WITH GESTATIONAL HYPERTENSION DURING PREGNANCY, CHILDBIRTH, POSTPARTUM, NEWBORN, AND FAMILY PLANNING AT PMB HANNA SIMBOLON, MEDAN 2026 - Agelia, Feby; Dewi, Eva Ratna; butar -butar, Minar Br.; Pasaribu, Riska Susanti; Simbolon, Hanna (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Continuity of care (CoC) is a continuous healthcare service between midwives and patients provided to women from early pregnancy, labor, postpartum, newborn, through to family planning. Gestational hypertension is a condition where a pregnant woman experiences blood pressure of 140/90 mmHg during pregnancy.Objectives: This study aims to expand knowledge in providing midwifery care for pregnancy, labor, postpartum, newborn, and family planning using Helen Varney’s 7-step midwifery management approach and SOAP notes.Methods: This study used a descriptive observational case study method to obtain a comprehensive overview of health phenomena within a specific population and individual in pregnant women starting from pregnancy with Gestational Hypertension, Labor, Postpartum, Newborn, and contraception in PMB Hanna Simbolon, Medan Labuhan District, Medan City, 2026.Results: During pregnancy, the mother experienced gestational hypertension at 21 weeks of gestation, requiring treatment and 6 antenatal care (ANC) visits. The labor was a normal vaginal delivery on February 10, 2026, delivering a female infant. Postpartum care from the 2nd to the 4th visit (KF 2 to KF 4) was conducted appropriately without complications. Neonatal visits from the 2nd to the 3rd visit (KN 2 to KN 3) proceeded well without issues. The mother opted for an implant contraceptive method, and no problems were found.Conclusions: Care was provided continuously, and no gaps were found between theory and practice in the case of Mrs. P at PMB Hanna Simbolon, Medan Labuhan District, Medan City, 2026.